Varicela grave: An analysis of compulsory notifications, Brazil 2012 to 2019 (Research, Society and Development, 2021)
Objective: To describe and analyze the reported cases of severe varicella in Brazil and its social impact on public health. Methodology: This is a transversal observational descriptive study conducted with data collected by DATASUS, based on the survey of sociodemographic and clinical variables, from 2012 to 2019, and analyzed using prevalence calculations and the chi-square association test. Results: Of the 694,809 cases of severe varicella reported in Brazil, 2013 had the highest number of cases (28.51%), with a reduction in 2013 compared to 2019 (91.3%) and an increase of 55,36% from 2018 to 2019. Most cases were male, ranging from 51.15% to 52.31% (p